2008
DOI: 10.1038/embor.2008.8
|View full text |Cite
|
Sign up to set email alerts
|

Reptin and Pontin function antagonistically with PcG and TrxG complexes to mediate Hox gene control

Abstract: Pontin (Pont) and Reptin (Rept) are paralogous ATPases that are evolutionarily conserved from yeast to human. They are recruited in multiprotein complexes that function in various aspects of DNA metabolism. They are essential for viability and have antagonistic roles in tissue growth, cell signalling and regulation of the tumour metastasis suppressor gene, KAI1, indicating that the balance of Pont and Rept regulates epigenetic programmes critical for development and cancer progression. Here, we describe Pont a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 25 publications
2
49
0
2
Order By: Relevance
“…Although RVB1 and RVB2 are complexed with each other in cells, there are several examples where the two proteins act independently of each other (43,44,45,46). The rescue of TIP60.com's HAT activity by either rRVB1 or rRVB2, however, suggests that the two proteins can also function alone and are redundant with each other.…”
Section: Discussionmentioning
confidence: 90%
“…Although RVB1 and RVB2 are complexed with each other in cells, there are several examples where the two proteins act independently of each other (43,44,45,46). The rescue of TIP60.com's HAT activity by either rRVB1 or rRVB2, however, suggests that the two proteins can also function alone and are redundant with each other.…”
Section: Discussionmentioning
confidence: 90%
“…The Uri complex probably contributes to the control of gene expression via the E3-ubiquitin ligase SCF Skp2 and its association with RNA polymerase II and the Paf complex (Adelman et al, 2006). Furthermore, Reptin in Drosophila is a component of the PRC1 complex (Qi et al, 2006), whereas Pontin purifies with the Brahma chromatin remodeling complex (Diop et al, 2008). Reporter gene assays demonstrated that Pontin and Reption antagonistically influence the transactivation potential of the ß-catenin-TCF complex, which is central to Wingless signaling (Bauer et al, 2000).…”
Section: The Myst Hat Dtip60 Is Part Of a Multiprotein Complexmentioning
confidence: 99%
“…The cleared lysates were loaded onto a StrepTactin-Sepharose column (1-ml bed volume; IBA) by filtering through 0.45-m-pore-size polyethersulfone filter (Corning) and fractionated according to the manufacturer's instructions. The peak NS5A fraction from 30 preparations (12.5 g) was collected and concentrated by acetonemethanol precipitation and subjected to multidimensional protein identification technology (MudPIT) analysis (5,8,9,11,26,34,39,41). For the details of MudPIT analysis, see Materials and Methods in the supplemental material.…”
Section: Methodsmentioning
confidence: 99%